Utilização de sílica coloidal como método de auxílio na seleção espermática para criopreservação do sêmen canino - DARCÁDIA, Hugo Pieve (2017)
This study aimed to compare the canine semen characteristics after thawing of a semen centrifuged conventionally and in colloidal silica. 36 semen samples from six healthy dogs were evaluated about the motility, vigor, concentration, morphology and hyposmotic test. The ejaculate was divided into two equal fractions and centrifuged in colloidal silica and by the conventional method and subsequently cryopreserved. The centrifuged semen presented similar results (p<0,05) between both treatment, like motility (84,72±8.44 vs 83.89±9.93%), vigor (3.97±0.84 vs 4.19±0.71), concentration (270.71±109.05 vs 263.71±90.50cels/mL), normal cells (93.60±4.24 vs 92.97±4.61%) and hyposmotic test (90.26±4.75 vs 90.53±4.42%) for the control group and colloidal silica respectively. After thawing the samples from the two experimental groups were examined for computerized analysis parameters and differences (p<0.05) were observed between the groups for the Curvilinear velocity, values (63.07±22.94 vs 82.29±27.84μm/s), Progressive linear velocity, (21.79±4.60 vs. 26.85±9.10μm/s), Average velocity (36.39±9.94 vs. 45.68±10.16μm/s), Linearity (37.06±8.60 vs 31.68±9.80%) and Rectilinearity (61.09±6.48 vs 56.09±7.26%) for the control group and colloidal silica respectively. It can be concluded that pre-freezing centrifugation using colloidal silica is as effective as conventional seminal centrifugation, and may be an alternative generating results similar to those already established in the literature.